Comparative genomics analysis and molecular characterization of community and hospital-associated methicillin-resistant Staphylococcus aureus - Suhaili, Zarizal (2019)
Published genomics data regarding CA-MRSA and HA-MRSA isolates from Malaysia are scarce. Therefore, the aim of this study was to characterise the Malaysian CA-MRSA and HA-MRSA isolates in depth using molecular typing, as well as whole-genome sequencing. CA-S. aureus isolates were obtained from the nasal swabs of undergraduate students whereas HA-S. aureus isolates were archived samples obtained from hospital laboratories. Out of 168 S. aureus nasal carriage isolates obtained, the occurrence of MRSA was 8.3% and 15% among undergraduate students of the agriculture biotechnology and health sciences programmes, respectively, with multidrug resistance were observed in 15% (26/168) of the isolates. Among the 146 hospital archived samples of S. aureus, 28% (41/146) were MRSA, out of which 63% (i.e. 26/41) were categorised as multidrug-resistant (MDR; resistant to three or more classes of antimicrobial compounds). The most predominant SCCmec type among both CA- and HA-MRSA was SCCmec-III, with the highest occurrences observed among HA-MRSA (68%; 28/41) compared to CA-MRSA (41%; 9/22) isolates. Other SCCmec types that were found in CA-MRSA were SCCmec-IV (32%), SCCmec-I (23%), and SCCmec-II (4%), while in HA-MRSA were SCCmec-IV (22%), SCCmec-V (7%), and SCCmec-I (2%). spa type t037 was the most predominantly found among CA-MRSA (50%) and HA-MRSA (61%). Higher occurrence of the pvl gene (which encodes the pore-forming Panton-Valentine leucocidin) at 27% (11/41) among HA-MRSA compared to CA-MRSA at 23% (5/22). Another virulence factor, the staphylococcal surface protein gene (sasX), was more prevalent in HA-MRSA at 61% (25/41) compared with CA-MRSA (50%; 11/22). Nine S. aureus isolates representing HA-MRSA (SAZ_1, SAZ_10, SAZ_16, SAZ_31, and KT/Y21), hospital-associated methicillin-susceptible S. aureus (HA-MSSA, M314250), and CA-MRSA (ZS_Z30, ZS_Z37 and ZS_Z46) were subjected to wholegenome sequence analysis. Genomic content of all isolates were diverse with the presence of various mobile genetic elements (MGEs) such as insertional sequence (IS), transposons, plasmids, genomic islands (νSAα and νSAβ), phages, Staphylococcal pathogenicity islands (SaPIs: SaPI1, SaPI2, SaPI3, and SaPI5) as well as both virulence and resistance determinants. In-silico, MLST and spa type of nine representative isolates revealed five sequence types (ST)-spa types combinations, i.e. ST1-t127 (M314250), ST30-t122 (SAZ_31), ST239-t037 (SAZ_10, ZS_Z30, ZS_Z37, and ZS_Z46), ST239- t421 (SAZ_1), and ST772-t657 (SAZ_16 and KT/Y21). Interestingly, one of the HAMRSA isolates, SAZ_10, harboured a novel 35 kb conjugative plasmid designated pSAZ10A that carried multiple antimicrobial resistance (AMR) determinants (aadD, ileS, and tcaA) as well as complete conjugative transfer (tra) genes. Genome analyses showed the presence of multidrug efflux pumps and AMR genes, which were likely to contribute to the MDR phenotypes in these isolates. Moreover, various virulence factors were revealed among both CA and HA-MRSA isolates, which were likely to play essential roles in their pathogenesis. Pan-genome analysis of all representative isolates and other 49 global reference strains revealed an open genome with a large accessory genome allowing acquisition of exogenous DNA and facilitating successful adaptation to the selective hospital and community environment. Thus, this analysis provided us an insight into the characteristics and adaptability related to both virulence and resistance of MRSA and MSSA of Malaysian isolates, which will assist in the surveillance, prevention and control of pathogenic S. aureus particularly in community- and hospital-associated environment.